2016
DOI: 10.5152/iao.2016.2565
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Analysis of Paper Patch Myringoplasty in Patients with Tympanic Membrane Perforations

Abstract: OBJECTIVE:The aims of our study were to evaluate the outcome of office-based paper patch grafting in tympanic membrane (TM) perforation regardless of the disease duration or etiology and to compare the clinical factors influencing the successful closure of perforation between the success and failure groups of paper patch myringoplasty. MATERIALS and METHODS:This is a retrospective study of 114 patients that underwent paper patch myringoplasty in an outpatient setting (success group, 83 cases; failure group, 31… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
0
5
1
Order By: Relevance
“…The success rate of procedure in our study is 91.2% which is similar to or better than that reported by various authors. 11,[14][15][16][17][18][19] However, our general success rate is lower than that reported by Lou et al 17 In their study, almost 98% of 504 cases with traumatic TM perforations were acute onset (within 1 month after a trauma), and a spontaneous healing rate of 89% cases was reported. In our study, all perforations with traumatic etiology healed well, whereas the ones in which the procedure failed had inflammatory etiology.…”
Section: Discussioncontrasting
confidence: 57%
“…The success rate of procedure in our study is 91.2% which is similar to or better than that reported by various authors. 11,[14][15][16][17][18][19] However, our general success rate is lower than that reported by Lou et al 17 In their study, almost 98% of 504 cases with traumatic TM perforations were acute onset (within 1 month after a trauma), and a spontaneous healing rate of 89% cases was reported. In our study, all perforations with traumatic etiology healed well, whereas the ones in which the procedure failed had inflammatory etiology.…”
Section: Discussioncontrasting
confidence: 57%
“…Twenty‐two studies reported outcomes of paper patches for repair of TM perforations 13–34 . Several different types of paper were utilized, including rice paper, cigarette paper, and paper patch (not otherwise specified).…”
Section: Resultsmentioning
confidence: 99%
“…The remaining studies were either EBM level 3 (33%) or level 4 (34%). The mean score of the 41 nonrandomized studies assessed using the MINORS system was 13 ± 4 (range, [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Forty percent of all RCTs were investigations of paper patch grafting.…”
Section: Study Selection and Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Two articles investigated the predictive factors of fat graft myringoplasty (FGM) [37,41] and one article investigated paper patch myringoplasty [42]. These methods differ from traditional techniques, because the tympanomeatal flap is not elevated during the procedure.…”
Section: Fat Graft and Paper Patch Myringoplastymentioning
confidence: 99%